2021
DOI: 10.1002/jbm.a.37199
|View full text |Cite
|
Sign up to set email alerts
|

Physical and biological properties of electrospun poly(d,l‐lactide)/nanoclay and poly(d,l‐lactide)/nanosilica nanofibrous scaffold for bone tissue engineering

Abstract: Electrospun scaffolds exhibiting high physical performances with the ability to support cell attachment and proliferation are attracting more and more scientific interest for tissue engineering applications. The inclusion of inorganic nanoparticles such as nanosilica and nanoclay into electrospun biopolymeric matrices can meet these challenging requirements. The silica and clay incorporation into polymeric nanofibers has been reported to enhance and improve the mechanical properties as well as the osteogenic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 93 publications
1
11
0
Order By: Relevance
“…In bone TE, electrospinning has been widely used to produce nanofibrous scaffolds with a structure close to the nanoscale collagen fibers of bone [ 166 ]. Electrospun PLLA scaffolds were produced using a surface modification to direct cellular differentiation to the bone lineage and achieve optimal bone regenerative performances.…”
Section: Applications Of Plla-based Scaffold In Tissue Engineeringmentioning
confidence: 99%
“…In bone TE, electrospinning has been widely used to produce nanofibrous scaffolds with a structure close to the nanoscale collagen fibers of bone [ 166 ]. Electrospun PLLA scaffolds were produced using a surface modification to direct cellular differentiation to the bone lineage and achieve optimal bone regenerative performances.…”
Section: Applications Of Plla-based Scaffold In Tissue Engineeringmentioning
confidence: 99%
“…The process of bone formation occurs independently on separate surfaces and leads to procedures that may change the size, shape, and mass of the bone 29 . Bone has a unique ability to repair itself when the injury is not extensive, chronic, severe, or problematical 30 . Moreover, bones add proper structure, manage mechanical movement, protect organs, and produce blood cells 31 .…”
Section: Structure Materials and Mechanical Properties In Natural Bon...mentioning
confidence: 99%
“…This is due to these NPs having a few fascinating properties, such as low thermal conductivity, chemical inertness, and non‐toxicity. The results suggests that AS and CLO nanoparticles embedded in PLA electrospun matrix created good surroundings for cells development, presumably because the cells had a higher affinity for the substrate 30 . Another study found that adding cellulose nanocrystal (CNC) to the PLA matrix increases the mechanical properties of composite scaffolds while enhancing biocompatibility and nanocomposite scaffolds exhibited higher mechanical and thermal properties than polymer‐only scaffolds.…”
Section: Synthetic Polymers Scaffolds and Their Blends With Biopolyme...mentioning
confidence: 99%
“…Electrospinning involves the production of continuous fibers from inducing the charged filaments of polymer solutions by using an electric force directed by a highvoltage system equipped with a syringe connected to a metallic needle, a pressure pump, and a grounded stationary or rotating collector [81][82][83]. The liquid solution, pumped into the syringe, flows up to onto a pendent droplet suspended at the needle tip, which is then stretched continuously to form a cone-like structure, called the Taylor cone, while increasing the applied voltage.…”
Section: Electrospinningmentioning
confidence: 99%